Practices for reporting and responding to test results during medical consultations: Enacting the roles of paternalism and independent expertise - Pomerantz, Anita; Rintel, Sean (Discourse Studies, 2004)
When physicians take readings of health indices such as temperature or blood pressure, the practices that physicians and patients employ in discussing the readings both reflect and propose a set of expectations regarding the level of technical medical information the patients should acquire and understand. In this article we demonstrate how physicians’ reporting practices reflect and propose the roles of paternalism or independent expertise and how patients’ responding practices either ratify or contest the roles cast by the physicians’ practices. In contrast to the usual assumption that roles are relatively stable for individuals over the course of encounters, we treat role enactments as matters that are negotiated turn by turn in interaction. Physicians’ practices for reporting test results implicate various sets of expectations about the knowledge, interest, and responsibility state of each participant; patients employ responding practices that ratify or contest the expectations implicated by the physicians’ prior report. In each subsequent turn within the information exchange sequence, a speaker indicates (explicitly or implicitly) whether the level and kind of information being exchanged is appropriate/inappropriate and sufficient/insufficient for the participants.